2006
DOI: 10.7748/nop.18.8.27.s17
|View full text |Cite
|
Sign up to set email alerts
|

Depression and older people

Abstract: Nearly a third of older people admitted for acute hospital care experience depression. Rates of depression are even higher in care homes. The purpose of this article is to raise awareness among nurses of this debilitating condition and its potentially fatal consequences, and to suggest interventions that can bring about improvement. Although challenging for nurses, detecting and treating depression can bring enormous benefits for older people and, in some cases, can mean the difference between life and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…2005, Cheung et al. 2006, Waugh 2006, Conwell & Thompson 2008). Other factors associated with suicide in older people are alcohol use disorder, neurological illness, malignancy, multiple illnesses (O’Connell et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2005, Cheung et al. 2006, Waugh 2006, Conwell & Thompson 2008). Other factors associated with suicide in older people are alcohol use disorder, neurological illness, malignancy, multiple illnesses (O’Connell et al.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of suicideprevention studies thus far have focused on identifying characteristics of suicidal persons to enhance prediction of suicidal behaviours. The most important predictor of suicide among older people is depression (Chiu et al 2004, O'Connell et al 2004, Tsoh et al 2005, Cheung et al 2006, Waugh 2006, Conwell & Thompson 2008. Other factors associated with suicide in older people are alcohol use disorder, neurological illness, malignancy, multiple illnesses (O'Connell et al 2004), suicide ideation, mental illness, personality vulnerability, functional impairment, low resilience (Heisel 2006), hopelessness (Cheung et al 2006), loneliness and disconnectedness from the community (Cheung et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown clear relationships between depression and somatic conditions, such as heart, lung, and cerebrovascular diseases and diabetes (Engum 2007;Kvaal 2008;Mast et al 2005). Sociodemographic factors, such as advanced age, female sex, widowhood, living alone, and low education level, are also reported to be significantly related to anxiety and depression in older individuals living at home (Pettersen & Laake 2003;Waugh 2006). Feelings of helplessness, hopelessness, uselessness, loss of interest and energy, insomnia, and sleeplessness are common symptoms caused by mental problems in the older age group (Waugh 2006).…”
Section: Introductionmentioning
confidence: 99%
“…12,14 Depression is the most common cause of weight loss in older adults in community and institutional settings 5,12 because of the relationship between depression and anorexia and poor appetite in older adults. 7,15 Depression is a common problem and a significant cause of poor appetite and motivation to eat in older adults. 16 Although energy needs decrease as a result of aging, decreased intake as a result of decreased appetite can cause malnutrition.…”
mentioning
confidence: 99%